Designing a Solar-Powered IoT-Based Flood Early Warning System Prototype with Audio-Visual Alarm for Aceh Region - Muhammad Wali; Taufiq Iqbal; Abdus Salam; Syafrinal Syafrinal (Yayasan Pendidikan Mitra Mandiri Aceh (YPMMA), 2026)
Floods have repeatedly threatened the people of Aceh Province. Thousands of families lost their property and lives because the early warning information was delayed. This research designs a flood early warning system prototype based on IoT using renewable energy, which can operate on its own without PLN electricity. The system uses three IP68 float switch sensors to detect water levels at thresholds of 0.5m (normal), 1.0m (alert), and 1.5m (danger) combined with a 2-in-1 audio-visual alarm (strobe and siren) with a coverage distance of 100-150 meters. The energy design uses a solar panel of 50-100W with 12V DC voltage and has a minimum backup for 48 hours without sunlight. Hardware design, sensor accuracy testing, validation of the energy system, and testing the effectiveness of alarms are the research methods in this study which is conducted in Banda Aceh City. The results indicate that this system can run independently at low power consumption because float switch sensors are more effective than ultrasonic sensors under conditions where the water is turbid and full of debris as found in rivers in Aceh Province. This prototype is low-cost (less than Rp 2 million), requires minimal maintenance, and has high reliability; therefore, it can be adopted by communities that do not have many resources. This research provides a technical blueprint for developing an early warning system that fits geographically and climatically with Aceh Province which may be replicated in other flood-prone districts for disaster risk reduction programs.